2014
DOI: 10.1007/s10482-014-0282-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a type-2 diacylglycerol acyltransferase (DGAT2) from Rhodosporidium diobovatum

Abstract: Triacylglycerols (TAGs), synthesized in the microsomal membranes of eukaryotes, serve as a primary storage form of carbon and energy in microorganisms. For this reason, TAGs produced by organisms have great potential to become biofuels and facilitate researchers to look for alternative renewable sources of energy. The present study describes the identification and functional characterization of a type-2 diacylglycerol acyltransferase from Rhodosporidium diobovatum, designated as RdDGAT, which catalyzed the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The effect of substrate composition on the fatty acid profile of R. toruloides microbial oil has been highlighted also by previous studies [7,14]. Further research studies focused on proteomics and transcriptomics have demonstrated that gene expression and substrate specificity have a key role in lipid synthesis [41]. Specifically, Fillet et al mentioned that the final chain length of the fatty acid relates to the substrate preference of the elongase 3-ketoacyl-CoA [42].…”
Section: Resultsmentioning
confidence: 92%
“…The effect of substrate composition on the fatty acid profile of R. toruloides microbial oil has been highlighted also by previous studies [7,14]. Further research studies focused on proteomics and transcriptomics have demonstrated that gene expression and substrate specificity have a key role in lipid synthesis [41]. Specifically, Fillet et al mentioned that the final chain length of the fatty acid relates to the substrate preference of the elongase 3-ketoacyl-CoA [42].…”
Section: Resultsmentioning
confidence: 92%
“…1, RtDGATa was clustered within DGAT1 family and had substantial similarity with Acyl-CoA: Cholesterol acyltransferase from S. cervisiae (ScARE). However RtDGATb was distinctly separated into DGAT2 family and had the largest similarity with RdDGAT2 from R. diobovatum, which had been proved to belong to DGAT2 family (Chen et al, 2014). Multiple sequence alignment of DGAT2 from seven organisms was performed (Fig.…”
Section: Identification and Protein Sequence Analysis Of R Toruloidementioning
confidence: 99%
“…In addition, empty vector and pYES2-DGA1 harboring DGA1 from S. cervisiae were transformed into S. cervisiae H1246 as negative (HY1) and positive controls (HY2) respectively (Table 1). Meanwhile, A RdDGAT2from other red yeast R. diobovatum which had been discussed in previous study (Chen et al, 2014) was also considered as another positive control (HY3). The results of Western blot analysis showed that all proteins were expressed in S. cervisiae H1246 and their expression levels were undifferentiated (Fig.…”
Section: R Toruloides Dgats Recovered Tag Synthesis In S Cervisiae mentioning
confidence: 99%
See 1 more Smart Citation